Analisis Persamaan Transpor Sedimen terhadap Fenomena Perubahan Morfologi Sungai Progo Tengah - Mananoma, Tiny (Jurusan Teknik Sipil, Fakultas Teknik , UGM, 2006)
The Understanding abOout the changing phenome non in river morphology can be started with the study on the available data of measurements. This study can provide informations about the changes in the slopes and elevations of the river bed, the cross section areas, and the storage capacity in a certain river segment as the results of erosion and sedimentation processes. Hence an illustrqtion of the stabiliry condition of the Middle Progo river channel from the aspects of rate and pattern of sediment transport can be obtained. The understanding about this phenomenon is approached through several equations of sediment transport. The results of this study reveal that theformlilas of MPM, Einstein. Frijlink. Van Rijn, and Karim can explain the existing phenomenon of sediment transport in general, but the amount of differences' between the caculated / simulated values and the measurecl values are still significant. To obtain the simulated values close to the values of measurements, there are still a number of other factors besides those already in the formulas, which should be included in the calculations of sediment transport. These factors are considered as being also to be influencing.